Weathering intensity and trace elements (Ni, Sr, Zn, and Cr) distribution in Vertisols developed on basalt in a semiarid environment: agronomic implications - Eze, Peter N.; Ebouel, Ferdinand J. Dina; Nkonga, Itumeleng; Musiol, Antje; Schleicher, Anja M.; Günter, Christina; Norra, Stefan (Frontiers in Soil Science, 2025)
Chemical weathering, a major geomorphic process, controls soil formation and evolution at the Earth’s surface and is strongly influenced by prevailing environmental conditions. In this study, three weathering soil profiles on a prominent agricultural landscape in a semiarid environment, central Botswana, were investigated to ascertain how parent material and pedogenic processes influence soil geochemistry, especially trace element accumulation. The soils were characterized on the basis of their macromorphological, physicochemical, mineralogical, and geochemical properties via routine laboratory procedures. A suite of 11 weathering indices was used to quantify chemical weathering, whereas multivariate analysis was used to interpret the geochemical dataset and detect affinity groups of samples and pedogenic properties. The soils are generally deep (>100 cm) and predominantly fine-grained, given that 78% of the samples had sandy clay loam to clay textures. The soils are alkaline, with pH values ranging from 7.4-8.4. Silicon, Al, Fe, and Ca are the four most abundant elements in the soils, and their variation within and between the pedons reflects their mineralogical compositions: quartz, montmorillonite, quartz, calcite, and palygorskite. The applied weathering indices (CIA, CIW, PWI, PIA, ICV, RR, VR, and Rb/Sr ratios) indicate the soils are moderate to highly weathered. Most of the indices had strong correlations and should not be applied synchronously in soils developed from basaltic parent materials. Particle size distribution significantly affected the weathering indices. The average αAlMg, αAlCa, αAlNa, αAlSr, αAlK, αAlBa, and αAlRb values in the three pedons are 0.52, 0.66, 2.77, 1.91, 3.72, 1.21, and 3.80, respectively. Factor analysis of the geochemical affinity confirmed that clays and Fe–Mn oxide illuviation coupled with calcite nodule formation were the dominant pedogenic processes. Overall, the applied indices affirm that the soils developed on a uniform parent material, with low-K basalt and high concentrations of chromium. The distinct soil properties of Vertisols from Serowe confirm that the soils are polygenetic given the increasing dryness of the area.